2016
DOI: 10.1063/1.4942937
|View full text |Cite
|
Sign up to set email alerts
|

Tunable multimode electromagnetically induced absorption transmission in metal-insulator-metal resonators

Abstract: The tunable multimode electromagnetically induced absorption (EIA)-like transmission was investigated in a two-ring system. In this system, by introducing asymmetry factor δi = λr - λr′, we provided several ways to modulate the EIA-like transmission spectra. An off-to-on EIA-like response could be realized by changing the radius or the refractive index of the rings. During the off-to-on process, we found the red shift and blue shift effects in the spectra are appeared and the widths of EIA-like dips are broade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…On the contrary, in Fig 2(D) and 2(F) , the H y fields in the inside disk cavity is anti-phase with the fields in the input MIM waveguides, which leads to a resonance destructive and preventing the optical waves transmitting. Compared with the triple-cavity structure Meng et al[ 25 ] proposed and the double-ring structure Wang et al[ 19 ] prosed, the system we proposed is novel, simple and easy to be fabricated.…”
Section: Eia-like Response In Dual-resonator-coupled Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, in Fig 2(D) and 2(F) , the H y fields in the inside disk cavity is anti-phase with the fields in the input MIM waveguides, which leads to a resonance destructive and preventing the optical waves transmitting. Compared with the triple-cavity structure Meng et al[ 25 ] proposed and the double-ring structure Wang et al[ 19 ] prosed, the system we proposed is novel, simple and easy to be fabricated.…”
Section: Eia-like Response In Dual-resonator-coupled Systemmentioning
confidence: 99%
“…For example, Zhang et al[ 1 ] reported a classical analog of EIA in a three-resonator metasurface system and Tauberte et al[ 17 ] observed the EIA-like phenomenon by employing the benefits of near-field coupling and retardation effects due to far field coupling. These kind of classical analogs of EIA showed its potential applications such as ultra-narrow band perfect absorbers [ 18 ], optical modulation, and absorptive switching[ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhai et al investigate PIA and PIT spectra based on MIM waveguide coupled with a ring concentric resonator structure [11]. Liu et al designed multimode PIA based on a double-ring resonator coupled MIM waveguide [12]. In 2020, our group designed a tunable PIR effect based on a MIM waveguide resonator structure with liquid crystal material [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, hard operation conditions limit its development, and then alternative plasmon-induced transparency (PIT) effects that are analogous to the EIT effects, are demonstrated in various MIM waveguide structures [25,26,27]. Recently, plasmon-induced absorption (PIA), an opposite effect of the PIT effect, have been widely studied and demonstrated in the MIM structures [28,29,30]. Especially, PIA response is investigated in a MIM-based end-coupled composite-slot-cavity resonator [31].…”
Section: Introductionmentioning
confidence: 99%